RANCANGAN SCAFFOLDING BERDASARKAN HASIL TES KEMAMPUAN GEOMETRI SISWA SMP DITINJAU DARI PERLUASAN TEORI VAN HIELE - Fashihah Fashihah; Gatot Muhsetyo; Abd. Qohar (FMIPA UNIVERSITAS NEGERI MALANG, 2019)
The ability of geometry is an aspect that underlies students to solve geometry problems. Several studies have stated students' difficulties in learning geometry. There are five levels of expansion of Van Hiele's theory, namely level 0, level 0.5, level 1, level 1.5, and level 2 which are used to measure the geometry abilities of junior high school students. Students' low geometry skills can be improved through scaffolding, so an appropriate scaffolding design is needed. This study aims to describe the appropriate scaffolding design based on the geometry ability test of junior high school students in terms of the expansion of Van Hiele's theory. The research subjects in this study consisted of 3 students of class VIII of SMP Negeri 8 Malang divided into 3 different levels of geometry ability, namely level 0, 0.5, and 1. Data collection methods consisted of written tests and interviews. The results showed that students at level 1 needed scaffolding to be able to connect the properties between quadrilateral shapes. Students at level 0.5 require scaffolding in the form of conceptual understanding of prerequisite materials. While students at level 0 need scaffolding to minimize the prototype phenomenon.